Allopathic Medicine Practitioners' perspectives on facilitating disclosure of traditional medicine use in Gauteng, South Africa: a qualitative study - Lindiwe Gumede; Pauline B. Nkosi; Maureen N. Sibiya (BMC, 2023)
Abstract Background Traditional medicine (TM) plays a key role in maintaining health in many societies. Given the requirement for TM disclosure, Allopathic Medicine Practitioners (AMPs) must encourage open communication with patients to persuade those who use TM to disclose. Addressing patient non-disclosure of TM requires this dialogue to be facilitated. We sought to understand and describe how South African AMPs facilitate disclosure of TM use during a consultation with patients who use both TM and allopathic medicine (AM) and how it influences the patients' willingness to disclose TM use. Methods This qualitative exploratory descriptive study on AMPs at Gauteng district public hospitals in South Africa was conducted between 2021 and 2022. Non-probability purposive sampling was employed to select a sample of 14 AMPs. Individual participants were encouraged to share their unique experiences and interpretations of the phenomenon concerning TM use disclosure. The raw transcribed textual data were processed using ATLAS.ti, and inductive content analysis was undertaken following the coding of the content to identify categories. Results The data revealed four major categories: 'providing a suitable atmosphere for disclosure,' 'encouraging patients to disclose TM usage to AMPs,' 'patient autonomy,' and 'AMP training'. During a consultation with patients who use both TM and AM, participants expressed their experiences and perceptions of TM nondisclosure. They also discussed several methods for encouraging patients to disclose their TM usage, particularly when TM is used concurrently with AM. Conclusion This study expands on previously reported findings by describing how South African AMPs facilitate the disclosure of TM use during consultation. Many AMPs struggle to initiate TM conversations with their patients which results in non-disclosure. This study revealed that integrating TM into AM training programmes, promoting cross-practice, and creating a safe environment is necessary for the development and application of the most appropriate approaches that would assist in facilitating disclosure.